Influência do encruamento e tratamentos prévios na microestrutura de um aço SAE 1045, após tratamento térmico de esferoidização - Almeida, Dyego Irineu Silva de (2018)
The aim of this work was to evaluate the influence of hardening and previous thermic treatments on the microstrucuturesof a SAE 1045 steel, after spheroidizationheating treatment. Nine samples were separeted, where three of them were tempered and six were normalized. The normalized samples were plastically shaped with the aid of a hydraulic pressure in order to reduce their height by 10%. The hardness of the samples was measured and then subjected to a subcritical spheroidization treatment at 700 ° C. After five hours one sample of each group (normalized, deformed and tempered) were taken out of the oven and properly identified. The procedure now mentioned were repeated two more times, after ten hours of heat treatment then after twenty hours. After that, the hardness was measured again then the samples were prepared metallographically and their microstructures were analyzed. In evaluating the results, it was concluded that the previous tempered samples had better response related to spheroidization kinetics, showing better distributed carbides in the ferritic matrix, whereas the normalized and deformed ones only presented the spheroids after 10 hours of treatment, where it was observed carbides inside the grains of perlite. Lastly, normalized samples presented lower hardness at the end of the twenty hours of heat treatment.